Towards a More Inclusive Economy : Understanding the Barriers Sudanese Women and Youth Face in Accessing Employment Opportunities - Etang, Alvin; Lundvall, Jonna; Osman, Eiman; Wistrand, Jennifer (World Bank, Washington, DC, 2021)
The report is organized as follows. After a brief description of the analytical framing and methodology in section two, section three presents the history and demographics of the labor market in Sudan, focusing on indicators by gender and age across the three main sectors of employment: services, agriculture, and industry. Section four examines formal institutions: the institutional setting, service delivery, and laws and regulations as they relate to economic opportunities. Section five examines informal institutions, where the social norms and networks can be a barrier to women’s and youth’s full economic participation. Section six analyzes how the market is supporting or constraining economic activity, which includes a closer look at the labor market itself and access to assets. Section seven discusses how all of these aspects are considered when it comes to the household- and individual-level decision-making that directly affects women’s and youth’s accumulation of human capital, overall agency, and, ultimately, their economic opportunities. Section eight concludes with considerations for policy and action.